1984
DOI: 10.1111/j.1399-3054.1984.tb04601.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IAA‐induced ethylene production in etiolated mung bean hypocotyl segments by 2,3,5‐triiodobenzoic acid and 2‐(p‐chlorophenoxy)‐2‐methyl propionic acid

Abstract: 1984. Inhibition of IAA-indueed ethylene production in etiolated mung bean hypocotyl segments by 2,3,5-triiodoben2oic acid and 2-(pclilorophenoxy)-2-methyl propionic acid, -Physiol. Plant. 62: 448-452.The effect of two auxin antagonists, 2,3,5-triiodobenzoic acid (TIBA) and 2-(p-chIorophenoxy)-2-methyl propionic acid (CMPA) on IAA-indueed ethylene production in etiolated mung bean hypocotyl {Vigna radiata L. Rwiicz cv. Berken) segments was studied. Both TIBA and CMPA inhibited IAA-indueed ethylene production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
0
8
1
Order By: Relevance
“…Today the induction of ethylene by auxin is generally thought to be one of the most common plant-hormone interactions. In fact, it has been suggested that ethylene production by vegetative tissues is naturally regulated by the internal levels of auxin [1,2,26,30], although there is no direct evidence to support this idea. Sakai and Imaseki [22], working with etiolated mung beans, and Kang et al [11 ], studying etiolated pea segments, both showed that after a one-hour lag, the rate of ethylene production increased with time and this increase was dependent on the auxin concentration applied.…”
Section: Introductionmentioning
confidence: 85%
“…Today the induction of ethylene by auxin is generally thought to be one of the most common plant-hormone interactions. In fact, it has been suggested that ethylene production by vegetative tissues is naturally regulated by the internal levels of auxin [1,2,26,30], although there is no direct evidence to support this idea. Sakai and Imaseki [22], working with etiolated mung beans, and Kang et al [11 ], studying etiolated pea segments, both showed that after a one-hour lag, the rate of ethylene production increased with time and this increase was dependent on the auxin concentration applied.…”
Section: Introductionmentioning
confidence: 85%
“…On the other hand, the effect of PCIB was often attributed to the inhibition of auxin transport (Katekar and Geissler, 1980;Tsai and Arteca, 1984), the regulation of auxin metabolism (Frenkel and Haard, 1973), or nonspecific toxic effect (Yip and Yang, 1986). Although the effects of PCIB presented in this study such as inhibition of lateral root development, loss of gravitropic re- sponse, and inhibition of primary root growth are also caused by auxin influx or efflux inhibitors (Fujita and Syono 1996;Luschnig et al, 1998;Casimiro et al, 2001;Malamy and Ryan, 2001;Rahman et al, 2001Rahman et al, , 2002, some of the PCIB effects are crucially different from the effects of auxin influx and efflux inhibitors.…”
Section: Pcib Inhibits Auxin Responsementioning
confidence: 99%
“…It was reported that PCIB itself can inhibit polar auxin transport. [63][64][65] However, since the capacity of PAT was similar in the modern and older hybrids, we could possibly exclude differential inhibitory effects of PCIB on PAT in the hybrid seedlings.…”
Section: Discussionmentioning
confidence: 99%